Effects of moisture on the long-term performance of adhesively bonded FRP/steel joints used in bridges - Heshmati, Mohsen; Haghani, Reza; Al-Emrani, Mohammad (Composites. Part B, Engineering, 2016)
Concerns regarding the durability of adhesively-bonded fibre-reinforced-polymer (FRP)/steel joints in bridges have been a major obstacle to their growing application. On the one hand, the available long-term data of FRPs used in bridges is rare and, on the other hand, the existing assessment approaches have mainly been developed to address the needs of industries, such as the aviation sector, with distinct differences. This paper uses both experimental and numerical approaches to investigate the effects of moisture, as one of the most influential factors, on the long-term performance of FRP/steel joints used in bridges. Gravimetric measurements are used to characterise the 3D moisture-diffusion properties for different FRPs and an adhesive material in various ageing conditions. Fast curing of the adhesive was found to have no significant effect on the diffusion properties of fully cured epoxy specimens. Salt water was found to degrade the mechanical properties of adhesive to a lesser degree than distilled water. The tested double-lap-shear joints of FRP/steel showed ca. 5% strength gain after eight months and ca. 9% reduction in the failure load after 12 months of ageing. While the elastic modulus of adhesive was found to decrease significantly with increasing moisture content, the stiffness reduction was found to be trivial in the joint-level. The results of coupled diffusion-mechanical finite element analyses indicate the importance of adherend permeability on moisture ingression into the joints. Moreover, the presence of small amounts of moisture at the steel/adhesive interface for less than a critical period is found to increase the joint strength. However, prolonged exposure to the same moisture content degrades the strength of the joint, and is, thus, time dependent.